DAMPAK BERBAGI HIBURAN UNTUK NILAI-NILAI KONSUMEN PADA VIDEO KOMERSIAL DAN EKUITAS MEREK PADA MIXUE JAKARTA - Christian Niscal Ziliwu; Margaretha Pink Berlianto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
Internet users in recent years have experienced rapid growth due to rapid developments in technological devices, mobile applications, and internet connections. For Indonesia itself, the use of social media has also become a trend that is no less widely used. Mixue's ice cream and sweet drink outlets are "colonizing" all of Indonesia right now, and they are doing so not only offline but also online. This research has a quantitative research method, which emphasizes the use of data and facts related to the object and subject of research. Research with quantitative type with random sampling method with SemPLS analysis tool as a statistical tool to find information about the influence between variables in this study. The results of this study are in line with Souki et al. (2021) that there is no significant effect of brand attachment on brand equity. there is no significant and positive effect of entertainment value on likehood to share. There is a significant and positive effect of social value on likehood to share. There is a significant and positive effect of functional value on likehood to share. there is a significant and positive effect of likehood to share on brand attachment. There is a significant and positive effect of brand attachment on brand equity. There is a significant and positive effect of likehood to share on brand equity.